Integrated spatial and single cell transcriptomics identifies PRKDC as a dual prognostic biomarker and therapeutic target in hepatocellular carcinoma - Wenpeng Pang; Yunyong Wang; Xiaohang Lu; Minpeng Li; Fuli Long; Songlin Chen; Yuan Yu; Mingfen Li; Hongsheng Lin (Scientific Reports)
Abstract Hepatocellular carcinoma (HCC) is a leading cause of cancer-related mortality, with a pressing need for effective biomarkers and therapeutic targets. Despite the clinical use of alpha-fetoprotein (AFP) as a diagnostic biomarker, its limitations in sensitivity and specificity necessitate the identification of novel markers. In this study, we investigated the role of Protein Kinase, DNA-Activated, Catalytic Subunit (PRKDC) in HCC prognosis and its potential as a therapeutic target. Utilizing spatial transcriptomics and single-cell RNA sequencing (scRNA-seq), we dissected the cellular composition of PRKDC in HCC tissue samples, revealing its high expression in malignant cell subpopulations and its association with the tumor immune microenvironment. Through clinical signature analysis, we observed widespread PRKDC expression in HCC tissues, particularly in immune cells, highlighting its link to immune cell infiltration. Further analyses confirmed high PRKDC expression in malignant cells and its inhibitory effect on immune cell infiltration. Copy number variation (CNV) analysis revealed significant genomic instability, with PRKDC exhibiting both amplifications and deletions across chromosomal regions, underscoring its role in tumorigenesis. Functional overexpression of PRKDC in HCC cell lines enhanced cell proliferation, migration, and altered cell cycle dynamics, with a notable increase in the G2/S phase. Taken together, we first to integrate spatial transcriptomics and single-cell transcriptomics and bulk RNA-seq to reveal that PRKDC is a reliable prognostic biomarker and a potential therapeutic target. High PRKDC expression is associated with shorter survival times and an abnormal tumor microenvironment, highlighting its impact on immune cell infiltration and HCC prognosis. Targeting PRKDC could selectively inhibit its expression in tumor cells, providing new strategies for HCC treatment.